Accelerated progression of coronary artery calcification in hypertension but also prehypertension. Issue 11 (November 2016) - Lehmann, Nils; Erbel, Raimund; Mahabadi, Amir A.; Kälsch, Hagen; Möhlenkamp, Stefan; Moebus, Susanne; Stang, Andreas; Roggenbuck, Ulla; Strucksberg, Karl-Heinz; Führer-Sakel, Dagmar; Dragano, Nico; Budde, Thomas; et al.
Abstract : Objective: To determine the role of hypertension for coronary artery calcification (CAC) progression. Methods: The population-based Heinz Nixdorf Recall study recruited 4814 participants from a German urban population in 2000–2003. CAC was measured using electron-beam computed tomography at baseline and after 5 years. The present analyses refer to 3481 participants with repeat scan (coronary heart disease until 5 years excluded, age at baseline 45–74 years, and 53.1% women). Blood pressure (BP), Framingham risk factors, and antihypertensive medication were recorded at baseline. BP was staged according to Joint National Committee 7 guidelines. Participants under antihypertensive medication were classified as stage 2. CAC at 5 years was predicted from baseline using our dedicated, publicly available algorithm. CAC progression was accordingly classified as slow, expected, or rapid. Results: Normotension was found in 20.5%, prehypertension in 27.2%, stage 1 hypertension in 15.8%, and stage 2 (ST2) in 36.5%. The frequency of rapid progression increases with BP stage (normotension: 16.7% to ST2: 21.1%, P  = 0.004). Risk factor adjusted relative risk [RR (95% confidence interval), reference: normotension] of rapid progression was for prehypertension: 1.22 (0.98;1.51), stage 1: 1.29 (1.01;1.65), and ST2: 1.45 (1.17;1.79). Risk factor adjusted measures of CAC progression per 10 mmHg SBP were already elevated in women with BP below 140/90 mmHg: CAC onset, RR = 1.22 (1.07;1.40), rapid progression, RR = 1.17 (1.05;1.31), 5-year CAC progression, 6.7% (0.5;13.4). In men below 140/90 mmHg, only RR of rapid progression was considerably increased [RR = 1.11 (0.96;1.29)]. Conclusion: CAC progression, a sign of ongoing target organ damage, is already accelerated in prehypertensive patients, a substantial proportion of our urban population. Abstract : Supplemental Digital Content is available in the text